2010
DOI: 10.2478/v10057-010-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and attitudes of Polish students learning Hebrew

Abstract: SHOrt COMMUnICAtIOnSlimited studies have been carried out in Poland to investigate the motivation which is activated and maintained among Polish students learning Hebrew as their optional second language. the aim of this research was to examine the relationships among integrative and instrumental attitudes and motivation level (gardner, 1985a) in two age groups of students learning Hebrew, using an 18-item questionnaire adapted from the AMtb (gardner, 1985b). Contrary to expectations, gender and family ties d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Polish learners of Hebrew (Okuniewska et al, 2010). Moreover, instrumental motives were more common than intrinsic ones in a sample of dyslexic language learners (Csizér et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 84%
See 2 more Smart Citations
“…Polish learners of Hebrew (Okuniewska et al, 2010). Moreover, instrumental motives were more common than intrinsic ones in a sample of dyslexic language learners (Csizér et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 84%
“…It implies that the learner studies the language to become similar to members of the target language community (Gardner, 1985). In the Polish context, it has been found to predict effort invested in language learning (Okuniewska et al, 2010;Okuniewski, 2012) and even grades (Gardner, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on differences in motivation to learn foreign languages have shown stronger motivation among female than male learners. A slightly higher level of motivation among girls than boys has been established by research in different countries, including Canada (Kissau, 2006;Kissau et al, 2010), China (Ahåt, 2013), the United Kingdom (Williams et al, 2002), Hungary (Dörnyei et al, 2006), Korea (Kim & Kim, 2011), Poland (Okuniewska et al, 2010), Sweden (Henry, 2009), Turkey (Öztürk & Gürbüz, 2013;Polat, 2011) and the United States (Brantmeier et al, 2013;Chavez, 2014). Males were less motivated than females when learning various languages, for example English (Dörnyei et al, 2006;Henry, 2009;Kim & Kim, 2011;Ahåt, 2013;Öztürk & Gürbüz, 2013), French (Williams et al, 2002, Kissau, 2006Dörnyei et al, 2006), German (Williams et al, 2002, Dörnyei et al, 2006Chavez, 2014), Hebrew (Okuniewska et al, 2010), Italian (Dörnyei et al, 2006), Kurdish (Polat, 2011), Russian (Dörnyei et al, 2006) and Spanish (Kissau et al, 2010;Brantmeier et al, 2013).…”
mentioning
confidence: 97%
“…Russian pupils had a stronger desire to be good language learners and achieve native-like proficiency but lower actual L2 self-concept than Finnish pupils (Julkunen and Borzova 1997). Motivational research in Poland often adopted a Gardnerian approach (Gardner 2012;Okuniewska et al 2010;Okuniewski 2012Okuniewski , 2014. An exception to that was Pawlak (2012: 347), whose investigation into the dynamic nature of motivation revealed the presence of short and long-term fluctuations in interest and engagement, although no "meaningful changes in motivational intensity from one lesson to the next" were found.…”
Section: Comparison Of Finnishmentioning
confidence: 99%